Factores que influyen en la deserción de métodos anticonceptivos hormonales en adolescentes de 12 a 18 años de edad en el Centro de Salud Barreiro periodo febrero 2023 – junio 2024. - Gaibor Pesantes, Milena Dayana (2024)
Los Ríos, Ecuador. The personal, social and educational factors that influence the interruption of the use of these methods are explored. The research was carried out through surveys applied to 84 adolescents between 12 and 18 years of age, revealing that 100% have used hormonal contraceptive methods, but none of them currently use them. The results indicate that the main cause of side effects, such as irregular bleeding, heavy cramping and mood swings, while the influence of friends and partners also plays a significant role. In addition, there is a correlation between a low level of schooling and abandonment of these methods. Improving sex education and access to reliable information is essential to reduce dropout, as well as addressing fears related to side effects and strengthening family support. Improving sex education and access to reliable information is essential to reduce dropout, as well as addressing fears related to side effects and strengthening family support. The research concludes that hormonal contraceptive discontinuation among adolescents is influenced by personal, social, and educational factors, which highlights the need for comprehensive interventions that address both access and education in sexual and reproductive health.